The “accusatory/inquisitorial” dichotomy in the colombian context: a path towards an efficient transformation of the office of the Attorney General of the Nation - Gerenas Díaz, Luz Adriana; Cárdenas, Fernando (DIXI, 2024)
Law 2094 of 2021 presents us with a challenge: ensuring compliance with the principle of impartiality within administrative sanctioning processes. To address this, the application of the separation of functions is envisioned as a possible solution, in the strict sense in which it is ensured by the accusatory principle (typical of criminal law). This solution arises because, as a result of the historical-ontogenetic analysis, we find an analogy between the origins of the accusatory principle and Law 2094 of 2021; in turn, this analogy is conceptually supported by the “accusatory/inquisitive” dichotomy. In order to evaluate the viability of this proposal, a logical analysis is carried out to verify that there is no inconsistency between the legal logic of the two principles. Based on the foregoing, the logical consistency of the application of the accusatory principle to the normative framework established by Law 2094 of 2021 is evaluated. Finally, the logical consequences that this application would have and how it would respond to the guarantees required of the Office of the Attorney General of the Nation by the Inter-American Court of Human Rights will be presented.